Adaptation to Damaging Dance and Repeated-Sprint Activity in Women. Issue 9 (September 2016) - Brown, Meghan A.; Howatson, Glyn; Keane, Karen M.; Stevenson, Emma J.
Abstract : Abstract: Brown, MA, Howatson, G, Keane, KM, and Stevenson, EJ. Adaptation to damaging dance and repeated-sprint activity in women. J Strength Cond Res 30(9): 2574–2581, 2016—The repeated bout effect (RBE) refers to the prophylactic effect from damaging exercise after a single previous bout of exercise. There is a paucity of data examining the RBE in women, and investigations using exercise paradigms beyond isolated eccentric contractions are scarce. In light of the limited literature, this investigation aimed to determine whether 2 different sport-specific exercise bouts would elicit a RBE in women. Twenty-one female dancers (19 ± 1 years) completed either a dance-specific protocol ( n = 10) or sport-specific repeated-sprint protocol ( n = 11). Delayed-onset muscle soreness (DOMS), limb girths, creatine kinase (CK), countermovement jump height, reactive strength index, maximal voluntary contraction, and 30-meter sprint time were recorded before and 0, 24, 48, and 72 hours after exercise. An identical exercise bout was conducted approximately 4 weeks after the initial bout, during which time the subjects maintained habitual training and dietary behaviors. DOMS and 30-meter sprint time decreased after a second bout of both activities ( p = 0.003; = 0.38 and p = 0.008; and = 0.31, respectively). Circulating CK was also lower at 24, 48, and 72 hours after the second bout, independent of group ( p = 0.010 and = 0.23). Compared with the repeated-sprint protocol, the magnitude of change in DOMS was greater after a subsequent bout of the dance protocol ( p = 0.010 and = 0.19). These data are the first to demonstrate that dance and repeated-sprint activity resulting in muscle damage in women confers a protective effect against muscle damage after a subsequent bout.